“Dolls or teddies?”: constructing lesbian identity through community-specific practice. - Jones, Lucy (John Benjamins Publishing, 2014)
The concept of ‘community’ often presents a problem for queer linguists. ‘The gay community’ is often viewed as an impossible site for research due to its imagined status, whilst local communities of gay people have been considered too heterogeneous and idiosyncratic to draw conclusions from. In this article, however, it is argued that both of these aspects of community can, and should, be a central focus of an investigation into language and sexual identity. Through the analysis of a conversation emerging from a lesbian group, using a sociocultural linguistics framework, it is argued here that the community of practice approach can play a crucial role in understanding how ideologies from ‘the gay community’ are used to construct a coherent sexual identity on a local level. The analysis reveals how the group engages in practices that enable them to construct micro-level personas in direct response to broader, ideological structures of heteronormativity.